2019
DOI: 10.1097/sla.0000000000003626
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Compression After Endovenous Thermal Ablation of Varicose Veins (COMETA Trial)

Abstract: Background: The 21st century has witnessed a rise in the use of endovenous thermal ablation. Being highly clinically and cost-effective and improving the quality of life of patients, they are now considered to be the ''gold-standard'' treatment for varicose veins. Postintervention management, especially in terms of postoperative compression; however, remains unclear. As a result, a randomized study was undertaken to investigate the effects of wearing compression stockings after varicose vein treatment. Method:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 33 publications
(34 reference statements)
4
32
0
1
Order By: Relevance
“…Long-term follow-up studies would be necessary to evaluate long-term occlusion rates. Most of our patients returned to normal daily activities the same or the next day, which is in accordance with other studies [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Long-term follow-up studies would be necessary to evaluate long-term occlusion rates. Most of our patients returned to normal daily activities the same or the next day, which is in accordance with other studies [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in this study, a bare fiber was used in combination with an 810 nm diode laser. Bootun et al reported a significantly lower median pain score after the EVLA of saphenous veins in a compression group on days 2-5, compared to a no compression group in the COMETA trial [13]. Patients with additional phlebectomies and compression stockings had significantly lower pain scores on days 1-3, day 5, and day 7 compared to those who did not undergo compression [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vyrų), kuriems buvo taikyta ELT, viena grupė devėjo kompresines kojines, o kita nenaudojo jokių kompresinių priemonių. Rezultatai skelbia, jog kojinių dėvėjimas sumažino pooperacinį skausmą, kojų tinimą ir prisidėjo prie greitesnio fizinių kojos funkcijų atkūrimo [20].…”
Section: Konservatyviojo Gydymo Metodaiunclassified